2008
DOI: 10.1002/mawe.200800286
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the electroplating parameters on the conditions of deposited nickel‐iron coatings

Abstract: Several specific electroplating parameters are varied to develop a manufacturing process for nickel-iron coatings with low residual stresses and favourable structures and hardness values. Here, the produced coating conditions on the surface are characterised according to alloy compositions, microstructures, residual stresses, texture and microhardness as well as the elastic indentation modulus. The manufacture of the coatings was carried out in a laboratory electroplating plant. The process parameters are: ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In was concluded that integration of both rapid prototyping and rapid tooling techniques have been proved to be an efficient way of fabricating micro-featured hot embossing stamps with conformal cooling channels without the use of copper ducts [16]. In addition, the proposed method requires no expensive apparatus compared to methods such as photolithography [17], wire electrical discharge machining [18], focused ion beam [19], electrochemical micromachining [20], deep-reactive ion etching [21], micro machining [22], micro-electro discharge machining [23], laser micromachining [24], lithographie galvanoformung abformung [25], and silicon-based micromachining [26]. However, optimal designs of conformal cooling channels for reducing the cycle time of hot embossing have not been carried out.…”
Section: Resultsmentioning
confidence: 99%
“…In was concluded that integration of both rapid prototyping and rapid tooling techniques have been proved to be an efficient way of fabricating micro-featured hot embossing stamps with conformal cooling channels without the use of copper ducts [16]. In addition, the proposed method requires no expensive apparatus compared to methods such as photolithography [17], wire electrical discharge machining [18], focused ion beam [19], electrochemical micromachining [20], deep-reactive ion etching [21], micro machining [22], micro-electro discharge machining [23], laser micromachining [24], lithographie galvanoformung abformung [25], and silicon-based micromachining [26]. However, optimal designs of conformal cooling channels for reducing the cycle time of hot embossing have not been carried out.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decades, many scientific and technical studies have been carried out to account for the effects of factors on electroplating performance and to address the enhancement of nickel electroplating process (Abd El Wahaab et al, 1986;Dolgikh et al, 2009;Njau et al, 1998;Tsuru et al, 2002;Hoffmann et al, 2008;Gupta et al, 2002;Yoshida et al, 2003Yoshida et al, , 2004Abdel-Hamid, 1998;Wang et al, 2008;Shpanko et al, 2004;Badarulzaman et al, 2009;Balakai et al, 2009;Sotskaya and Dolgikh, 2008;Mohanty et al, 2001;Ciszewski et al, 2004;Oliveira et al, 2006;Orinakova et al, 2006). However, it is worth to mention that most of such investigations dealt with conventional methodology of experimentation in which one factor is varied while others are fixed at constant levels.…”
Section: Introductionmentioning
confidence: 97%
“…One of the challenges of this project was to determine the morphology of the deposited Ni (as a baseline) and Ni-Fe samples as previous literature values do not appear to be consistent (Buchheit et al 2006;Ebrahimi and Li 2003;Erb et al 1995Erb et al , 2003Hoffmann et al 2008;Song et al 2006). The value of the Ni deposit is that it can be readily electroplated in easy-to-handle electrolytes using well-known processes.…”
Section: Introductionmentioning
confidence: 98%